Coating forming method and coating material set
The sequential application of specific coating materials with optimized resin and scaly particle ratios addresses the extensibility issues of mica-based coatings, resulting in a durable and aesthetically pleasing film with enhanced followability and reduced roughness.
Patent Information
- Application Number
- JP2021086841
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-25
- Filing Date
- 2021-05-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-05-24
AI Technical Summary
Coatings formed from coating materials containing colored mica (scaly particles) exhibit poor extensibility, leading to easy peeling and cracking due to their cleavability, which limits their ability to follow the displacement of the base material.
A film forming method involving the sequential application of a first coating material and a second coating material, where the first material forms a base layer with specific resin and powder components, and the second material forms a design layer with scaly particles of varying sizes, optimized by weight ratios to enhance followability and aesthetics.
The method results in a coating with excellent followability to the base material, providing a natural stone-like appearance with reduced roughness and improved durability.
Smart Images

Figure 0007603526000001 
Figure 0007603526000002 
Figure 0007603526000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel method for forming a coating. [Background technology]
[0002] Conventionally, decorative finishing methods that impart the aesthetic appearance of natural stone to buildings and civil engineering structures have been known. In recent years, there have been an increasing number of cases where decorative finishing with design features such as the diverse colors peculiar to natural stone is desired. For example, Patent Document 1 describes such a method in which a resin mixed with colored mica (scale-like particles) of multiple colors is applied to a base material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-262134 Summary of the Invention [Problem to be solved by the invention]
[0004] However, coatings formed from coating materials containing colored mica (scale-like particles) as in Patent Document 1 tend to have poor elongation. In particular, layered compounds such as mica tend to peel off due to their cleavage. As a result, they cannot follow the displacement of the base, and there is a risk that cracks, peeling, etc. may occur easily.
[0005] The present invention has been made in consideration of the above-mentioned points, and has an object to provide a coating formation method capable of forming a coating that has excellent conformability to the base and excellent aesthetic appearance. [Means for solving the problem]
[0006] As a result of intensive research into solving the above problems, the inventors came up with the idea of a coating method in which at least two specific coating materials are applied in sequence, and have completed the present invention. That is, the present invention has the following characteristics.
[0007] That is, the present invention has the following features. 1. A coating forming method for applying a first coating material and a second coating material to a substrate in that order, The first coating material is a resin component. (A) Powder component per 100 parts by weight of solid content (B) Contains 70 to 1000 parts by weight, The second coating material is a resin component. (C) For 100 parts by weight of solid content, scaly particles (D) Contains 5 to 200 parts by weight of fruit, The coating forming method, characterized in that the scale-like particles (D) include large particles (d1) having a short diameter of more than 2 mm, medium particles (d2) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (d3) having a short diameter of 0.7 mm or less. 2. The method for forming a coating according to 1., wherein the weight ratio of the medium particles (d2) and small particles (d3) to the large particles (d1), [(d2)+(d3)] / (d1), is 1 or more and 50 or less. 3. A coating material set for forming a laminate coating, comprising: The coating set includes at least a first coating material and a second coating material, The first coating material is a resin component. (A) For 100 parts by weight of solids, powder components (B) Contains 70 to 1000 parts by weight, The second coating material is a resin component. (C) For 100 parts by weight of solid content, scaly particles (D) Contains 5 to 200 parts by weight of fruit, The coating material set is characterized in that the scale-like particles (D) include large particles (d1) having a short diameter of more than 2 mm, medium particles (d2) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (d3) having a short diameter of 0.7 mm or less. 4. The coating material set according to claim 3, characterized in that the weight ratio [(d2)+(d3)] / (d1) of the medium particles (d2) and small particles (d3) to the large particles (d1) is 1 or more and 50 or less. Effect of the Invention
[0008] According to the present invention, a coating film having excellent conformability to the base and excellent appearance can be formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described.
[0010] The present invention relates to a coating forming method, which is characterized by sequentially applying a specific first coating material and a specific second coating material to a substrate. First, the first coating material and the second coating material will be described.
[0011] <First covering material> The first coating material of the present invention contains a resin component (A) and a powder component (B), and is a coating material that forms a base layer. The resin component (A) (hereinafter also referred to as "component (A)") is not particularly limited, but is preferably at least one selected from water-soluble resins and water-dispersible resins (resin emulsions). Examples of the resin include vinyl acetate resins, polyester resins, alkyd resins, vinyl chloride resins, epoxy resins, acrylic resins, urethane resins, acrylic silicone resins, fluororesins, and the like, or composites thereof. These can be used alone or in combination of two or more. In addition, these components (A) may have crosslinking reactivity. When a component (A) having crosslinking reactivity is used, the water resistance, weather resistance, chemical resistance, and the like of the coating can be improved.
[0012] In the present invention, it is preferable that the component (A) contains an acrylic resin emulsion (A1). Furthermore, the acrylic resin emulsion (hereinafter also referred to as "component (A1)") preferably contains, as a resin constituent, an alkyl (meth)acrylate ester (p) (hereinafter also referred to as "component (p)") having an alkyl main chain having 3 or more carbon atoms. In the present invention, the alkyl acrylate ester and the alkyl methacrylate ester are collectively referred to as an alkyl (meth)acrylate ester.
[0013] The (p) component has an alkyl main chain with 3 or more carbon atoms in the alkyl portion. This alkyl main chain is linear and does not include cyclic chains. As long as the (p) component has such an alkyl main chain, it may have various side chains (e.g., alkyl groups with fewer carbon atoms than the alkyl main chain). Examples of the (p) component include n-propyl (meth)acrylate, isobutyl (meth)acrylate, 1-ethylpropyl (meth)acrylate, t-pentyl (meth)acrylate, neopentyl (meth)acrylate, n-butyl (meth)acrylate, 2-methylbutyl (meth)acrylate, isopentyl (meth)acrylate, 3-methylbutyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, n-pentyl (meth)acrylate, 2-methylpentyl (meth)acrylate, 4-methylpentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, and n-lauryl (meth)acrylate. These can be used alone or in combination of two or more. Among these, the component (p) is preferably one having an alkyl main chain with 4 or more carbon atoms (more preferably 4 to 8) in the alkyl portion.
[0014] The component (p) is preferably contained in the resin constituents of the component (A1) at 20% by weight or more (more preferably 25 to 70% by weight, and even more preferably 30 to 60% by weight). By containing the component (p) in such a ratio, conformability to the base can be improved. In the present invention, "α to β" is synonymous with "α or more and β or less".
[0015] The (A1) component may contain a monomer other than the (p) component (hereinafter also referred to as "(q) component") as a resin constituent. Examples of the (q) component include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, or a carboxyl group-containing monomer, an amino group-containing monomer, a pyridine-based monomer, a hydroxyl group-containing monomer, a nitrile group-containing monomer, an amide group-containing monomer, an epoxy group-containing monomer, a carbonyl group-containing monomer, an alkoxysilyl group-containing monomer, and an aromatic monomer. These may be used alone or in combination of two or more. The content of these (q) in the resin constituents of the (A) component is preferably 80% by weight or less (more preferably 10 to 75% by weight, more preferably 15 to 70% by weight).
[0016] As the (A1) component, an acrylic silicone resin (A1') (hereinafter also referred to as "(A1') component") containing a silicone resin can be used. As such an (A1') component, one containing a silicone resin in emulsion particles of the (A1) component can be used. The silicone resin may be in a state of being mixed with the acrylic resin in the emulsion particles, or may be in a state of being chemically bonded to the acrylic resin. The use of such an (A1') component containing a silicone resin is preferable in terms of improving the effects of the present invention.
[0017] Silicone resin (hereinafter also referred to as "component (s)") can be obtained by polymerizing silicone components such as siloxane compounds and alkoxysilane compounds. Examples of siloxane compounds include cyclic siloxane compounds, linear siloxane compounds, and branched siloxane compounds. Examples of cyclic siloxane compounds include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane. Examples of alkoxysilane compounds include silane compounds having one or more alkoxyl groups in the molecule, such as tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, and dimethyldimethoxysilane, as well as silane coupling agents such as vinylmethyldimethoxysilane, γ-(meth)acryloyloxytrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-glycidoxypropyltrimethoxysilane. These can be used alone or in combination of two or more. The component (s) is contained in the resin constituting component (A1') in an amount of preferably 0.5 to 30% by weight (more preferably 1 to 25% by weight).
[0018] The component (A1) can be produced, for example, by emulsion polymerization of a monomer group containing the component (p) and, if necessary, the component (q). The component (A1') containing the component (s) can be produced, for example, by emulsion polymerization of a monomer group containing the component (p) and, if necessary, the component (q) in the presence of the component (s). For the emulsion polymerization, a known method can be used.
[0019] As the polymerization method, a known method may be adopted, and in addition to normal emulsion polymerization, soap-free emulsion polymerization, feed emulsion polymerization, seed emulsion polymerization, etc. may also be adopted. During the polymerization, an emulsifier, an initiator, a dispersant, a polymerization inhibitor, a polymerization retarder, a buffer, a chain transfer agent, etc. may be used.
[0020] As the emulsifier, various surfactants that can be used in emulsion polymerization can be used, and these may be reactive types (reactive surfactants) having polymerizable unsaturated double bonds. As the emulsifier, anionic surfactants and nonionic surfactants may be used alone or in combination.
[0021] The glass transition temperature (hereinafter simply referred to as "Tg") of the component (A) is preferably set to -50°C to 50°C. If Tg is within this range, the effects of the present invention can be stably obtained. In the present invention, Tg is a value calculated by Fox's formula. In addition, the average particle size of the component (A) is preferably 300 nm or less (more preferably 20 to 200 nm). If the average particle size is within this range, the water resistance, weather resistance, chemical resistance, etc. of the coating can be improved. In addition, the average particle size referred to here is a value measured by dynamic light scattering.
[0022] The powder component (B) (hereinafter also referred to as "component (B)") is not particularly limited, but includes a color pigment (b1) and a powder component other than a color pigment (b2), etc. These can be used alone or in combination of two or more.
[0023] The color pigment (b1) (hereinafter also referred to as "component (b1)") is a component that can impart color, hiding power, etc. to the first coating material. Examples of component (b1) include inorganic chromatic pigments such as ferric oxide (red oxide), yellow iron oxide, ultramarine, and cobalt green; organic chromatic pigments such as azo, naphthol, pyrazolone, anthraquinone, perylene, quinacridone, disazo, isoindolinone, benzimidazole, phthalocyanine, and quinophthalone; black pigments such as carbon black, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and black iron oxide; white pigments such as titanium oxide, zinc oxide, and alumina; and other luster pigments (pearl pigments, aluminum pigments, metallic pigments, etc.), phosphorescent pigments, and fluorescent pigments. These can be used alone or in combination of two or more. The average particle size of the component (b1) is preferably 1 μm or less (more preferably 0.01 to 0.9 μm). The average particle size of the color pigment is measured by a laser diffraction particle size distribution measuring device.
[0024] Examples of the powder component other than the color pigment (hereinafter also referred to as "component (b2)") include heavy calcium carbonate, light calcium carbonate, kaolin, clay, china clay, diatomaceous earth, hydrous fine powdered silicic acid, talc, mica, barite powder, barium sulfate, precipitated barium sulfate, barium carbonate, magnesium carbonate, silica powder, aluminum hydroxide, and other extender pigments; silica particles, kansui stone, diatomaceous earth, silica stone, silica sand, gravel, glass beads, resin beads, metal particles, and aggregates such as crushed rocks, glass, ceramics, shells, sintered bodies, concrete, mortar, plastics, rubber, and the like. These may be colored. These can be used alone or in combination of two or more.
[0025] In addition, the particle diameter of the (b2) component is preferably 1 to 1000 μm (more preferably 5 to 850 μm, and even more preferably 10 to 600 μm). In addition, for example, when the powder particles (b2') having a particle diameter of 53 to 300 μm are contained in the total amount of the (b2) component at preferably 40% by weight or more (more preferably 45% by weight or more, and even more preferably 50% by weight or more), a coating having even better aesthetic appearance can be formed. The upper limit is preferably 100% by weight or less (more preferably 95% by weight or less, and even more preferably 90% by weight or less). Such an embodiment is more preferable in terms of improving the effects of the present invention. In addition, when the particle diameter of the (b2) component is more than 20 μm, it can be measured by sieving using a metal mesh sieve specified in JIS Z8801-1:2000. In addition, when it is 20 μm or less, it can be measured using a laser diffraction type particle size distribution measuring device.
[0026] The first coating material is characterized in that it contains 70 to 1000 parts by weight (preferably 100 to 800 parts by weight, more preferably 130 to 600 parts by weight) of component (B) per 100 parts by weight of solid content of component (A), thereby enabling the formation of a coating film with excellent conformability to the base.
[0027] In the present invention, the component (B) preferably contains 50% by weight or more of the component (b2) (more preferably 55 to 98% by weight, and even more preferably 60 to 95% by weight). By containing the component (b2) in such a ratio, the conformability to the substrate can be further improved. Furthermore, by containing the powder particles (b2') having a particle diameter of 53 to 300 μm, it is possible to form fine irregularities derived from the component (b2') on the surface of the base layer. This can further enhance the effects of the present invention and suppress the rough feeling derived from the jumping up of the ends of the scale-like particles in the design layer.
[0028] The first coating material can be produced by uniformly mixing the above-mentioned components by a known method, but if necessary, other components that can be used in normal coating materials can also be mixed in. Examples of such components include pigment dispersants, emulsifiers, thickeners, film-forming assistants, leveling agents, coupling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, dryness adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, defoamers, adsorbents, deodorizers, fibers, ultraviolet absorbers, light stabilizers, antioxidants, catalysts, crosslinking agents, etc.
[0029] <Second covering material> The second coating material of the present invention is a coating material that forms a design layer, and is characterized by containing a resin component (C) and scaly particles (D).
[0030] The resin component (C) (hereinafter also referred to as "component (C)") in the second coating material is not particularly limited, and a resin selected from the same resins as the component (A) of the first coating material can be used. These can be used alone or in combination of two or more. In the present invention, it is preferable that the component (C) contains an acrylic resin emulsion (C1). The acrylic resin emulsion (C1) (hereinafter also referred to as "component (C1)") preferably contains the above-mentioned component (p) as a resin component. The component (p) is preferably 1 to 50% by weight (more preferably 2 to 40% by weight, and even more preferably 5 to 35% by weight) of the components of the component (C1). In addition, the content of the component (p) in the component (C1) is preferably less than the content of the component (p) in the component (A1). This provides excellent conformability to the substrate and is also advantageous in terms of the strength, aesthetics, etc. of the formed coating.
[0031] The scaly particles (D) (hereinafter also referred to as "component (D)") impart an excellent design to the formed coating. In addition, component (D) is advantageous in terms of thinning and weight reduction of the formed coating. The present invention is characterized in that the scaly particles (D) are contained in an amount of 5 to 200 parts by weight (preferably 10 to 100 parts by weight, more preferably 15 to 80 parts by weight) per 100 parts by weight of the solid content of resin component (C). When the above range is satisfied, a coating having a design such as a natural stone look can be obtained.
[0032] Examples of such (D) components include inorganic pieces such as mica, sericite, clay, talc, plate-like kaolin, barium sulfate flakes, glass flakes, alumina flakes, shell pieces, and metal pieces, as well as rubber pieces, plastic pieces, and wood pieces. Also, examples include those that are used as base particles and are colored. The coloring treatment is not particularly limited, but examples include a method in which a colorant containing a pigment or dye is coated (or adsorbed) on the base particles, and a method in which the base particles are subjected to a baking treatment or the like. In the present invention, it is preferable to use mica that has been coated with a colorant (colored mica). One or more types of (D) components can be used in combination (one color or two or more colors), and various colors can be expressed. In the present invention, it is preferable to use colored scaly particles (scaly colored particles), particularly colored mica (colored mica).
[0033] The "scaly particles" in the present invention are not particularly limited as long as they are scaly (thin), but are preferably particles with an aspect ratio (ratio of "minor diameter / thickness") of 1.5 to 2000 (more preferably 2 to 500, and even more preferably 3 to 100). In addition, it is preferable that the ratio of the minor diameter to the major diameter (minor diameter / major diameter) is 0.3 to 1 (more preferably 0.4 to 1, and even more preferably 0.5 to 1). When the size of the scaly particles satisfies the above range, the shape is easily visible and is suitable for design. Furthermore, a design layer excellent in terms of thinning and weight reduction can be formed. The "minor diameter", "major diameter", and "thickness" mentioned here are calculated by placing the scaly particles stably on a horizontal surface and observing them from above using a microscope, with the length of the shortest part being the "minor diameter", the length of the longest part being the "major diameter", and the maximum height from the bottom being the "thickness".
[0034] In the present invention, the component (D) preferably contains large particles (d1) having a minor axis of more than 2 mm (hereinafter also referred to as "large particles (d1)"). By containing the large particles (d1), a large pattern design can be effectively imparted to the formed coating.
[0035] Furthermore, it is preferable that the (D) component contains, in addition to the large particles (d1), medium particles (d2) (hereinafter also referred to as "medium particles (d2)") having a short diameter of more than 0.7 mm and 2 mm or less, and small particles (d3) (hereinafter also referred to as "small particles (d3)") having a short diameter of 0.7 mm or less. By using the (D) components of different sizes in combination in this way, it is possible to suppress the jumping up of the ends of the (D) component, and it is possible to form a coating film with less roughness and excellent flatness and aesthetics, and it is possible to form a coating film with good balance (arrangement) of the pattern without the unevenness of the scale-like particles. This makes it possible to impart colors such as natural stone and designs such as large patterns, and it is advantageous in terms of increasing the strength of the coating film and following the base. Specifically, the medium particles (d2) are mainly visually recognized as the base pattern (base color) of the coating film. Furthermore, the small particles (d3) are a component that imparts a small design to the formed coating and also imparts hiding properties and the like to the formed coating.
[0036] In the present invention, it is preferable to use the large particles (d1), the medium particles (d2), and the small particles (d3) in combination at a specific weight ratio, and it is preferable that the weight ratio [(d2)+(d3)] / (d1) of the medium particles (d2) and the small particles (d3) to the large particles (d1) is 1 or more and 50 or less (more preferably 3 or more and 40 or less, and even more preferably 5 or more and 30 or less). When such a range is satisfied, the large particles (d1) are less likely to be biased, and a coating having excellent aesthetics and a good balance (arrangement) of the large pattern by the large particles (d1) can be formed in the base pattern formed by the medium particles (d2) and the small particles (d3). Furthermore, the medium particles (d2) and the small particles (d3) can sufficiently suppress the end jumping of the large particles (d1), and a flat coating with even less roughness can be formed. Furthermore, the weight ratio (d2) / (d3) of the medium particles (d2) to the small particles (d3) is preferably 1 or more and 30 or less (more preferably 1.5 or more and 20 or less, and even more preferably 2 or more and 10 or less). When such a range is satisfied, the above-mentioned effects can be further enhanced.
[0037] The mechanism of action by which such an effect is obtained is not limited, but for example, the medium particles (d2) and small particles (d3) smaller than the large particles (d1) act as spacers for the large particles (d1) and contribute to the dispersibility of the large particles (d1). In addition, the small particles (d3) smaller than the medium particles (d2) act as spacers for the medium particles (d2) and contribute to the dispersibility of the medium particles (d2). As a result, it is presumed that the (D) component dispersed in the coating material can maintain good dispersibility for the large particles (d1), medium particles (d2), and small particles (d3). In particular, it is presumed that in a coating material containing a relatively large amount of medium particles (d2), the large particles (d1) and small particles (d3) are dispersed in a well-balanced manner in the medium particles (d2). It is presumed that by applying such a coating material, the particles are less likely to be biased, a coating with a well-balanced pattern is formed, and the jumping up of the particle ends can be sufficiently suppressed.
[0038] In the present invention, the minor axis of component (D) refers to the length of the shortest part when the scale-like particles are stably placed on a horizontal surface, as described above, and the large particles (d1), medium particles (d2), and small particles (d3) can be classified by sieving using a metal mesh sieve (standard sieve) specified in JIS Z8801-1:2000. In this case, if the opening of the standard sieve is "a", the length of the diagonal line "L = √2a" can be considered to correspond to the minor axis. Specifically, 100 g of component (D) is weighed out and sieved for 10 minutes using a test method (manual sieving) in accordance with JIS K 0069, Large particles (d1) are those that do not pass through a 12 mesh (a=1.4mm, L=2.0mm) sieve. Those that pass through a 12 mesh (a=1.4mm, L=2.0mm) sieve but do not pass through a 30 mesh (a=0.5mm, L=0.7mm) sieve are called medium particles (d2), Those that pass through a 30 mesh (a=0.5mm, L=0.7mm) sieve are small particles (d3), Let us assume that. The upper limit of the large particles (d1) is preferably those that pass through a 6.5 mesh (a=2.8 mm, L=4.0 mm) sieve (particles with a minor axis of 4 mm or less), while the lower limit of the small particles (d3) is preferably those that do not pass through a 70 mesh (a=0.21 mm, L=0.3 mm) sieve (particles with a minor axis of more than 0.3 mm).
[0039] In the present invention, the component (D) may be monochromatic (one color only) or multi-colored depending on the desired design. When the component (D) is monochromatic (one color only), a coating having a pattern derived from the shape of each particle can be obtained.
[0040] When the (D) component is of a plurality of colors, it is preferable that the component contains particles of at least two or more colors (more preferably, two to six colors). This allows a coating film to have a pattern derived from the shape of each particle and a design such as a variety of colors. The embodiment in which the (D) component contains two or more colors can be set according to the desired pattern (design). In the present invention, it is preferable that the large particles (d1) and the medium particles (d2) contain particles of different colors. This allows the large accent design to be effectively recognized, and a coating film with excellent aesthetics can be easily formed. In addition, it is preferable that the small particles (d3) contain particles of the same color system as the large particles (d1) or the medium particles (d2) (more preferably, the medium particles (d2)). This gives the formed coating a sense of depth, and the aesthetics can be further improved.
[0041] Moreover, the large particles (d1), the medium particles (d2), and the small particles (d3) may each contain particles of two or more colors. In particular, when the large particles (d1) contain two or more colors, the sense of variegation is improved, and the aesthetic appearance can be further enhanced. When the medium particles (d2) contain two or more colors, it is preferable that the medium particles (d2') that become the base pattern (base color) of the formed coating are contained in the medium particles (d2) at 50% by weight or more (more preferably 55% by weight or more). The medium particles (d2') may contain two or more types of particles of a single color (only one color) or similar colors (similar colors). This makes the accent design by the large particles (b1) easier to see, and the aesthetic appearance can be improved. Furthermore, when the small particles (b3) are of two or more colors, it is preferable that the small particles (d3') which become the base pattern (base color) of the formed coating and have the same color system as the hollow particles (d2') account for 60% by weight or more (more preferably 65% by weight or more) of the small particles (d3).
[0042] In the above component (D), a different color refers to a color difference (ΔE) of preferably 10 or more (more preferably 15 or more). Also, the same color system (similar or similar colors) refers to a color difference (ΔE) of preferably less than 10 (preferably 8 or less). The color difference (ΔE) referred to here is a value measured using a color difference meter, and can be calculated from the respective L*, a*, and b* values according to the following formula. <Formula>△E={(L *1 -L *2 ) 2 +(a *1 -a *2 ) 2 +(b *1 -b *2 ) 2} 0.5 During the ceremony, L *1 , a *1 , b *1 are the first color of the (B) component, L * , a * , b * . L *2 , a *2 , b *2are the second color of the (B) component, L * , a * , b * . Furthermore, the L*, a*, and b* of component (D) can be calculated by placing component (D) on a glass plate until the glass surface is covered, and then covering the surface with a PE film (colorless and transparent).
[0043] The second coating material of the present invention can be produced by uniformly mixing the above-mentioned components by a known method, but if necessary, other components that can be used in normal coating materials can also be mixed in. Examples of such components include color pigments, extender pigments, fibers, film-forming assistants, thickeners, leveling agents, coupling agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, antifoaming agents, UV absorbers, light stabilizers, antioxidants, water, etc.
[0044] The coating material of the present invention is preferably an aqueous coating material. The pH of the coating material is preferably 7 to 12 (more preferably 7.5 to 11). In such a range, the effect of the present invention can be sufficiently enhanced. Furthermore, the non-volatile content of the coating material is preferably 10 to 80% by weight (more preferably 15 to 70% by weight). In such a range, it is possible to obtain a formed coating film that has the design characteristics such as the diverse colors unique to natural stone, and has a flat and excellent aesthetic appearance with little roughness. The non-volatile content can be adjusted by adjusting the compounding ratio of each component, etc.
[0045] <Film formation method> The coating film forming method of the present invention is characterized in that the first coating material and the second coating material are applied to a substrate in this order. For example, (1) applying a first coating material to a substrate to form a base layer; (2) A step of applying a second covering material onto the base layer to form a design layer; This makes it possible to form a laminated coating (laminated pattern coating) in which a base layer and a design layer are laminated.
[0046] The substrate constitutes the surface of buildings, civil engineering structures, etc. Examples of such substrates include concrete, mortar, siding boards, extrusion molding boards, gypsum boards, slate boards, perlite boards, plywood, bricks, plastic boards, metal boards, glass, and porcelain tiles. These substrates may have a coating already formed on the surface, or may have wallpaper attached thereto. In addition, the substrate may be subjected to a surface treatment as necessary. Examples of the surface treatment include filler treatment, putty treatment, surfacer treatment, and sealer treatment.
[0047] In the above step (1), before applying the first coating material, the substrate may be subjected to a surface treatment, if necessary. Examples of the surface treatment include a filler treatment, a putty treatment, a surfacer treatment, a sealer treatment, etc.
[0048] The first coating material in (1) above is the first coating material described above. The first coating material can be applied by, for example, spray coating, roller coating, trowel coating, brush coating, or a combination of these methods.
[0049] The first coating material can be applied once or multiple times. The first coating material is preferably applied once or twice. The amount of the first coating material applied is preferably 0.05 to 1 kg / m per application. 2 (More preferably 0.1 to 0.8 kg / m 2 By applying the first coating material under such conditions, a base layer suitable for application of the second coating material can be formed, making it easier to obtain the effects of the present invention.
[0050] When applying the first coating material, a diluent such as water can be mixed to adjust the viscosity as appropriate. The dilution ratio is preferably 0 to 20% by weight. The viscosity of the first coating material to be applied is preferably 3 to 30 Pa·s (more preferably 4 to 20 Pa·s), and the thixotropy index is preferably 2 to 9 (more preferably 3 to 8). The viscosity and thixotropy index referred to here are values obtained using a BH type viscometer as a measuring instrument (measurement temperature 23°C). The viscosity is a measured value when the rotation speed is 20 rpm. The thixotropy index is a value obtained by dividing the measured value at a rotation speed of 2 rpm by the measured value at a rotation speed of 20 rpm.
[0051] The first coating material may be dried preferably at room temperature (0 to 40° C.). When the first coating material is applied multiple times, it is desirable to apply the subsequent first coating material after the coating of the previous first coating material has dried.
[0052] In the above step (2), a second coating material is applied onto the base layer formed in the above step (1) to form a design layer. The above-mentioned second coating material is used as the second coating material. The second coating material can be applied by, for example, spray coating, roller coating, trowel coating, brush coating, etc. In the present invention, spray coating and roller coating are preferred, and it is particularly preferred to form a coating by spray coating using a spray. This makes it possible to easily form a coating that is flat and has excellent aesthetics, with less bias in the scaly particles (D), a good balance (arrangement) of the pattern, and little roughness.
[0053] The amount of the second coating material of the present invention to be applied is not particularly limited, but is preferably 0.05 to 1 kg / m per application. 2 (More preferably 0.1 to 0.8 kg / m 2 The number of times of application can be set depending on the desired design, but is preferably 1 to 2 times (more preferably 2 times). In such a case, the effect of the present invention can be fully exhibited.
[0054] When applying the second coating material, the viscosity can be adjusted appropriately by mixing a diluent such as water. The dilution ratio is preferably 0 to 20% by weight. The viscosity of the second coating material to be applied is preferably 1 to 50 Pa s (more preferably 5 to 40 Pa s), and the thixotropy index is preferably 3 or more (even more preferably 4 to 10).
[0055] The second coating material may be dried preferably at room temperature (0 to 40° C.). When the second coating material is applied multiple times, it is desirable to apply the subsequent second coating material after the previous coating film of the second coating material has dried.
[0056] In the coating film forming method of the present invention, a clear layer can be provided by applying a clear coating material to the outermost surface (on the design layer) for the purpose of surface protection, improving weather resistance, stain resistance, etc., as long as the effects of the present invention are not impaired. Such a clear layer may be either colorless and transparent or colored and transparent, and may be either glossy or matte (including 70% gloss, 50% gloss, 30% gloss, etc.).
[0057] <Covering material set> The coating material set of the present invention is used in the coating method and is characterized by comprising the first coating material and the second coating material. By using such specific coating materials in combination, a laminated coating (laminated pattern coating) that is excellent in conformity to the substrate and has an excellent appearance can be formed. EXAMPLES
[0058] The following examples will clarify the features of the present invention.
[0059] -Manufacture of the first coating material Based on the formulation shown in Table 1, the raw materials were mixed in a standard manner to produce primers 1 to 11. The following components were used:
[0060] (A) Resin component The weight ratios of the (p) component, the (q) component, and the (s) component in the resin constituent components are expressed as the “p ratio,” the “q ratio,” and the “s ratio,” respectively. Resin (A1-1): Acrylic resin emulsion (emulsion polymer of methyl methacrylate, t-butyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and methacrylic acid, p ratio: 42% by weight, q ratio: 58% by weight, average particle size: 140 nm, solid content: 50% by weight, medium: water) Resin (A1-2): Acrylic resin emulsion (emulsion polymer of methyl methacrylate, t-butyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, and silicone resin, p ratio: 42% by weight, q ratio: 38% by weight, s ratio: 20% by weight, average particle size: 145 nm, solid content: 50% by weight, medium: water) Resin (A1-3): Acrylic resin emulsion (emulsion polymer of methyl methacrylate, t-butyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and methacrylic acid, p ratio: 14% by weight, q ratio: 86% by weight, average particle size: 140 nm, solid content: 50% by weight, medium: water)
[0061] (B) Powder component Color pigment (b1): Dispersion of titanium oxide, solid content: 70% by weight Powder component (b2-1): Calcium carbonate (particle diameter 20 to 38 μm) Powder component (b2-2): Silica powder (particle size 20 to 400 μm, content of particle size 53 to 300 μm: 75% by weight) Powder component (b2-3): Silica powder (particle size 20 to 400 μm, content of particle size 53 to 300 μm: 45% by weight) Additives (thickeners, dispersants, defoamers, film-forming agents, etc.)
[0062] [Table 1]
[0063] -Manufacture of second coating material Based on the formulation shown in Table 2, the raw materials and additives (thickener, dispersant, defoamer, film-forming aid, etc.) were mixed by a standard method to produce second coating materials 1 to 13. The following components were used.
[0064] (C) Resin component Resin (C1): Acrylic resin emulsion (emulsion polymer of methyl methacrylate, 2-ethylhexyl acrylate, and cyclohexyl methacrylate, p ratio: 30% by weight, q ratio: 60% by weight, average particle size: 140 nm, solid content: 50% by weight, medium: water) (D) Scaly particles (d1) Large particles (d1-1) Black mica piece [minor diameter: over 2 mm and less than 4 mm, minor diameter / major diameter (average value): 0.95, minor diameter / thickness (average value): 11.4] (d1-2) White mica piece [minor diameter: over 2 mm and less than 4 mm, minor diameter / major diameter (average value): 0.88, minor diameter / thickness (average value): 10.7] (d1-3) Light cream-colored mica pieces [minor diameter: over 2 mm and less than 4 mm, minor diameter / major diameter (average value): 0.92, minor diameter / thickness (average value): 11.5] (d2) Medium particle (d2-1) Gray mica piece [minor diameter: over 0.7 mm and less than 2 mm, minor diameter / major diameter (average value): 0.87, minor diameter / thickness (average value): 10.5] (d3) Small particles (d3-1) Gray mica pieces [minor diameter: over 0.3 mm and less than 0.7 mm, minor diameter / major diameter (average value): 0.92, minor diameter / thickness (average value): 11.4] (d3-2) White mica piece [minor diameter: over 0.3 mm and less than 0.7 mm, minor diameter / major diameter (average value): 0.94, minor diameter / thickness (average value): 11.0] (others) Additives (thickeners, defoamers, film-forming agents, UV absorbers, etc.)
[0065] [Table 2]
[0066] <Test Example I> (Examples 1 to 9, Comparative Examples 1 to 3) The test substrate was made by placing two board-shaped wall materials (ceramic siding boards) side by side and filling the joints between the boards (width 10 mm x thickness 10 mm) with a modified silicone sealant. The first coating material (1-11) was applied to the entire surface of the test substrate in an amount of 0.3 kg / m 2 and dried at 23°C for 5 hours. Next, the second coating material 1 was applied with a spray gun (diameter: 5.5 mm) at a coating amount of 0.7 kg / m 2 The test specimens were spray-painted with the coating material and dried and cured at 23°C for 24 hours, and the following evaluations were carried out. The evaluation results for the combination of the first and second coating materials are shown in Table 3.
[0067] Tracking Ability 1 The test specimen obtained by the above method was displaced horizontally by 1.5 mm (tensile speed: 2 mm / min) in a tensile tester under standard conditions, and the surface condition was observed to evaluate conformability. The conformability was evaluated on a four-level scale (A>B>C>D), with "A" being for no cracks and "D" being for cracks.
[0068] Tracking ability 2 The test specimen obtained by the above method was left in a 65° C. incubator for 7 days, and then the conformability was evaluated by the same method as above.
[0069] Good conformability to the substrate was observed in Examples 1 to 9. In particular, in Examples 3 to 6 and 8, colored patterned coatings were obtained that were free of cracks and had excellent conformability to the substrate.
[0070] Furthermore, Examples 3 to 6 and 8 were evaluated as follows. Tracking Ability 3 The specimen obtained by the above method was left in a 65°C incubator for 7 days, and then displaced 2 mm (tensile speed: 2 mm / min) in the horizontal direction using a tensile tester under standard conditions. The surface condition was observed to evaluate the conformability. The evaluation criteria were the same as above.
[0071] [Table 3]
[0072] <Test Example II> (Examples 6, 10 to 21, Comparative Example 4) Test specimens were prepared and evaluated in the same manner as in Test Example I. The combinations of the first and second coating materials and the results are shown in Table 4. Furthermore, the test specimens obtained by the above method were visually evaluated for aesthetics (appearance). Texture (touch) The coating that was formed was rated on a 5-point scale of A>B>C>D, with "A" being the least rough coating and "D" being the rough coating. ·Design Those with little bias in the scale-like particles and a well-balanced pattern were given an "AA" rating, while those with a poorer pattern were given a "D", and the evaluation was on a five-level scale from AA>A>B>C>D.
[0073] Examples 6, 10 to 21 had good substrate conformability. In particular, Examples 6, 10 to 17, and 20 had no cracks, excellent substrate conformability, and little roughness, and a colored pattern coating was obtained. Furthermore, Examples 6, 13 to 16 (particularly Examples 13 and 14) had no bias in the large, medium, and small scale-like particles, and a colored pattern coating with a good pattern balance could be formed.
[0074] [Table 4]
Claims
1. A coating forming method for sequentially applying a first coating material and a second coating material to a substrate, comprising the steps of: The first coating material contains 70 to 1000 parts by weight of a powder component (B) based on 100 parts by weight of a solid content of a resin component (A), The second coating material contains 5 to 200 parts by weight of scale-like particles (D) per 100 parts by weight of a solid content of a resin component (C), The coating forming method is characterized in that the scale-like particles (D) include large particles (d1) having a short diameter of more than 2 mm, medium particles (d2) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (d3) having a short diameter of 0.7 mm or less.
2. The coating forming method as described in claim 1, characterized in that the weight ratio [(d2) + (d3)] / (d1) of the medium particles (d2) and small particles (d3) to the large particles (d1) is 1 or more and 50 or less.
3. A coating material set for forming a laminate coating, comprising: The coating set includes at least a first coating material and a second coating material, The first coating material contains 70 to 1000 parts by weight of a powder component (B) based on 100 parts by weight of a solid content of a resin component (A), The second coating material contains 5 to 200 parts by weight of scale-like particles (D) per 100 parts by weight of a solid content of a resin component (C), The coating material set is characterized in that the scaly particles (D) include large particles (d1) having a short diameter of more than 2 mm, medium particles (d2) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (d3) having a short diameter of 0.7 mm or less.
4. The coating material set described in claim 3, characterized in that the weight ratio [(d2) + (d3)] / (d1) of the medium particles (d2) and small particles (d3) to the large particles (d1) is 1 or more and 50 or less.
Citation Information
Patent Citations
Granite pattern finishing method by spray coating
JP1994262134A
Preparation of coated alloy product with excellent corrosion resistance, adhesion and flip-flop properties
JP1999172202A
Heat insulating structure
JP2010216223A
Coating film laminated body
JP2012217893A
Laminate
JP2016179646A
